Investigation of edge impurity transport and divertor fluxes by toroidally localized lithium injection on EAST with EMC3-EIRENE. (2nd October 2019) - Xie, T; Dai, S Y; Sun, Z; Zuo, G Z; Hu, J S; Feng, Y; Wang, D Z
Abstract: Three-dimensional (3D) edge fluid transport code EMC3-EIRENE has been employed to study lithium transport in the scrape-off layer (SOL) of EAST with the toroidally localized lithium injection experiment. The simulated profiles of the density of the Li ions show that the Li 1+ ions mainly populate at the upper private region, while the Li 2+ and Li 3+ ions distribute at the upper X-point and upstream SOL regions. The synthetic 3D line-integrated LiII emission image obtained by EMC3-EIRENE is in reasonable agreement with the experimental profile measured by the CCD camera system on EAST. The impacts of the poloidal locations of Li injection (LI) have been studied to evaluate the variation of the Li impurity transport and emission behaviors, which shows a strong dependence on the poloidal position of LI. It is found that the LI at the outer midplane is the most effective location to radiate the power and reduce the heat flux deposition on the divertor targets, in comparison with the other poloidal injection locations.